Research Progress on the Role of Inflammasomes in Kidney Disease - Kun Chi; Xiaodong Geng; Chao Liu; GuangYan Cai; Quan Hong (Mediators of Inflammation)
Inflammasomes are multimeric complexes composed of cytoplasmic sensors, apoptosis-associated speck-like protein containing a caspase activation and recruitment domain (ASC or PYCARD), and procaspase-1 and play roles in regulating caspase-dependent inflammation and cell death. Inflammasomes are assembled by sensing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) and initiate inflammatory responses by activating caspase-1. Activated caspase-1 promotes the release of the inflammatory cytokines interleukin-1β (IL-1β) and IL-18 and eventually induces pyroptosis. Inflammasomes are closely related to kidney diseases. In particular, the NLRP3 (NACHT, LRR, and PYD domain-containing protein 3) inflammasome has been shown to cause acute and chronic kidney diseases by regulating canonical and noncanonical mechanisms of inflammation. Small-molecule inhibitors that target NLRP3 and other components of the inflammasome are potential options for the treatment of kidney-related diseases such as diabetic nephropathy. This article will focus on the research progress on inflammasomes and the key pathogenic roles of inflammasomes in the development and progression of kidney diseases and explore the potential of this intracellular inflammation to further prevent or block the development of the kidney disease.